Reasons behind the success of the “Islamic State” - Wojciechowski, Sebastian (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
Terrorism today entails a wide range of diverse threats. Currently, the most dangerous such threats are posed by ‘the “Islamic State” (IS). The aim of this paper is to identify the key factors for the dramatic rise of the “Islamic State” to power and significance. Its success has been the sum total of a number of diverse and mutually linked factors. Those fall into the two categories of endogenic reasons associated with the activities undertaken by the “Islamic State” and the exogenic factors, which apply to various developments and processes which have also contributed to IS advancement. Despite the “Islamic State” s loss of influence and resources, it is bound to continue to destabilize the international scene and pose a security threat for years to come. One should therefore give priority to learning about the reasons behind its success as such knowledge may help not only defeat IS but also prevent other Islamic and terrorist organizations from rising to power in the future.

Współczesny terroryzm ściśle związany jest z całym szeregiem różnorakich zagrożeń. Obecnie najważniejszym spośród nich jest „Państwo Islamskie” (PI). Celem tekstu jest wskazanie najważniejszych przyczyn, które doprowadziły do gwałtownego wzrostu siły oraz znaczenia „Państwa Islamskiego”. Są one sumą składową szeregu ściśle powiązanych ze sobą różnorodnych czynników. Można je podzielić na dwie główne kategorie obejmujące przyczyny endogenne związane z różnorakimi działaniami podejmowanymi przez „Państwo Islamskie” oraz źródła egzogenne obejmujące inne wydarzenia czy procesy, które także przyczyniły się do sukcesów PI. Pomimo kurczenia się wpływów „Państwo Islamskie” jeszcze długo będzie destabilizować sytuację międzynarodową i zagrażać bezpieczeństwu. Poznanie zatem źródeł jego sukcesów uznać należy za kwestę priorytetową, która może być pomocna nie tylko w pokonaniu PI, ale także uniknięciu wzrostu potęgi innych organizacji islamistycznych czy terrorystycznych w przyszłości.
Przyczyny sukcesów „Państwa Islamskiego”
Keywords: The “Islamic State”; IS; terrorism; causes of terrorism; al Qaeda; Państwo Islamskie; ISIS; terroryzm; przyczyny terroryzmu; Al-Kaida